Age and gender on dispositional forgiveness in the Aceh Community, Indonesia - Sari, Kartika; Sulistyani, Arum; Yusuf, Rusli; ., Ishak; Mawarpury, Marty; Khairani, Maya (Journal of Posthumanism, 2025)
Prolonged conflict history and tsunami disaster experienced by Acehnese potentially influenced their forgiveness. This study explores the effects of age and gender on Acehnese dispositional forgiveness. The sample consisted of 458 Acehnese (75% female and 25% male) aged 20-60 years living in Aceh province participated in this study. Data was collected using the Indonesian version of the Heartland Forgiveness Scale (HFS). ANOVA was used to examine the effects of age and gender on dispositional forgiveness. The results showed a statistically significant main effect of age on dispositional forgiveness. Acehnese older adults are more forgiving than younger adults, while gender does not affect dispositional forgiveness. Further analysis on the HFS subscale indicated the effect of age on forgiveness of others and forgiveness of situations. This study’s findings would be beneficial in serving as a foundation for developing mental health initiatives within the Acehnese community.